Impending Central Retinal Vein Occlusion - Steenbakkers, Michelle (Canadian Journal of Optometry, 2016)
Central retinal vein occlusion (CRVO) may present with varied clinical manifestations, ranging from mild blurred vision and scattered retinal hemorrhages to severe vision loss, optic nerve swelling, pronounced retinal hemorrhages, collateral retinal vessel formation and neovascularization. Impending CRVO, also known as partial CRVO, is a relatively poorly-defined sub-classification of the CRVO condition. Those affected are either asymptomatic or may complain of mild, often transient episodes of blurring of vision and present with venous dilation and tortuosity but only a few widely scattered flame-shaped retinal hemorrhages. As an impending CRVO may be the prodromal phase of an acute CRVO, this diagnosis requires careful monitoring of the patient for progression. The following case outlines the differential diagnosis, sequelae and inter-professional management of an impending central retinal venous occlusion.